2010
DOI: 10.1137/090777700
|View full text |Cite
|
Sign up to set email alerts
|

Wave Propagation in Multicomponent Flow Models

Abstract: Abstract. We consider systems of hyperbolic balance laws governing flows of an arbitrary number of components equipped with general equations of state. The components are assumed to be immiscible.We compare two such models; one in which thermal equilibrium is attained trough a relaxation procedure, and a fully relaxed model in which equal temperatures are instantaneously imposed. We describe how the relaxation procedure may be made consistent with the second law of thermodynamics.Exact wave velocities for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…• Energy balance: We observe that the df 5 model derived here is equivalent to the two-component version of the model considered in [17]. There, it was also shown that this two-component model, and hence the df 5 model, is equivalent to models studied in [28,35].…”
Section: The Five-equation Drift-flux Modelmentioning
confidence: 51%
See 3 more Smart Citations
“…• Energy balance: We observe that the df 5 model derived here is equivalent to the two-component version of the model considered in [17]. There, it was also shown that this two-component model, and hence the df 5 model, is equivalent to models studied in [28,35].…”
Section: The Five-equation Drift-flux Modelmentioning
confidence: 51%
“…The N -component version of this model was the main focus of [17]. For our present case of N = 2, the following eigenvalues were found:…”
Section: The Four-equation Drift-flux Modelmentioning
confidence: 68%
See 2 more Smart Citations
“…Such systems model many relevant physical problems, such as two-phase flows which are locally not in thermodynamic equilibrium [7,8,32,37]. The limiting process → 0 in systems in the form (55) was extensively analysed by Liu [24] and Chen et al [4], with a particular focus on the relationship between stability and wave propagation.…”
Section: Hyperbolic Relaxation Systemsmentioning
confidence: 99%